Strategy for Transitioning from Conventional Vehicles to Electric Vehicles (EV) Using SPACE Analysis Method - Basri Kinas Mappaseng; Rian Pranata; Hapzi Ali; Djuni Thamrin (Dinasti International Journal of Management Science, 2026)
The transition from conventional fossil fuel-based vehicles to electric vehicles (EV) is a crucial strategic step to address the energy crisis and reduce carbon emissions. The purpose of this study is to formulate a highly precise transition strategy for industries or regions in adopting electric vehicle trends using the Internal Factor Analysis Summary (IFAS), External Factor Analysis Summary (EFAS), and Strategic Position and Action Evaluation (SPACE) matrix analysis. This research combines quantitative and qualitative methods by identifying internal factors (strengths and weaknesses) and external factors (opportunities and threats) that affect the electric vehicle ecosystem. The weighting and rating results in the IFAS matrix (0.80) and EFAS matrix (0.67) indicate a strong internal position and a highly supportive external environment. In the SPACE matrix mapping (X-axis = 1.00 and Y-axis = 1.00), the strategic position of this transition lies in the Aggressive Quadrant (Quadrant I). This position indicates that the organization or industry possesses a strong competitive advantage and good financial stability to maximize market opportunities. Recommended alternative strategies include aggressive market penetration, innovative product development, and massive expansion of supporting infrastructure to accelerate the transition from conventional to electric vehicles.